The Influence of Creativity and Innovation on Competitive Advantage and Price as a Mediating Variable - Febrianti, R Adjeng Mariana (Almana : Jurnal Manajemen dan Bisnis, 2024)
The rapid growth of the creative economy has garnered significant attention from the government. The Kelom Geulis industry evolved its designs, incorporating airbrush and batik elements. Despite achieving recognition nationally and internationally, artisans struggled to diversify their designs, sustain innovation, adapt to changing consumer preferences, and standardize pricing. This research investigates the influence of creativity and innovation on competitive advantage through price within the Kelom Geulis Creative Industry in Gobras Village, Tasikmalaya City. An explanatory research approach was employed to elucidate causal relationships among variables through hypothesis testing. The study used Structural Equation Modeling (SEM) and Partial Least Squares (PLS) analysis to analyze the data. Data was collected from a purposive sample of 200 customers who purchased Kelom Geulis products. The findings demonstrate that creativity (t = 3.071, p = 0.002) significantly influences competitive advantage. Similarly, innovation (t = 8.177, p = 0.000) significantly affects competitive advantage. Additionally, price (t = 4.268, p = 0.000) plays a substantial role in shaping competitive advantage. Indirectly, creativity significantly influences competitive advantage through price (t = 2.299, p = 0.022), while innovation also significantly influences competitive advantage and Price as a mediating variable (t = 3.403, p = 0.000).